2017
DOI: 10.1002/cssc.201601884
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Three‐Dimensional NiFe/Cu2O Nanowires/Cu Foam Electrode for Water Oxidation

Abstract: Water splitting is of paramount importance for exploiting renewable energy-conversion and -storage systems, but is greatly hindered by the kinetically sluggish oxygen evolution reaction (OER). In this work, a three-dimensional, highly efficient, and durable NiFe/Cu O nanowires/Cu foam anode (NiFe/Cu O NWs/CF) for water oxidation in 1.0 m KOH was developed. The obtained electrode exhibited a current density of 10 mA cm at a uniquely low overpotential of η=215 mV. The average specific current density (j ) was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 62 publications
0
28
0
Order By: Relevance
“…One approach focuses on the optimization of the electronic structure of metals to improve the intrinsic activity of the catalysts, such as changing the valence state of the metal, and preparing multimetal materials by means of a doping method . Another approach is the application of substrates with large surface area and high conductivity, such as nickel foam (NF), copper foam (CF), various carbon materials, and metal substrates with carbon layers or Au layers . For metallic substrates, surface metal oxides and other impurities should be removed by acidic treatment before use in electrodeposition procedures .…”
Section: Figurementioning
confidence: 99%
“…One approach focuses on the optimization of the electronic structure of metals to improve the intrinsic activity of the catalysts, such as changing the valence state of the metal, and preparing multimetal materials by means of a doping method . Another approach is the application of substrates with large surface area and high conductivity, such as nickel foam (NF), copper foam (CF), various carbon materials, and metal substrates with carbon layers or Au layers . For metallic substrates, surface metal oxides and other impurities should be removed by acidic treatment before use in electrodeposition procedures .…”
Section: Figurementioning
confidence: 99%
“…However, the high overpotential and sluggish reaction kinetics of OER dramatically restricts the overall efficiency of energy conversion. Therefore, enormous efforts have been devoted to developing efficient electrocatalysts to reduce the overpotential and expedite the kinetics of the OER 5, 6, 7. To date, commercial electrocatalysts for OER still rely on the precious metal oxides, such as IrO 2 and RuO 2 .…”
mentioning
confidence: 99%
“…However, the low electron conductivity greatly impedes the electron transformation from catalyst surface to support electrode thus limits their OER efficiency. Recent study showed that the addition of Fe, Co or V, even in trace amount, was thought to greatly improve the OER activity of Ni‐based compounds due to the enhanced conductivity and strong synergistic effect in alkaline solutions though the complete mechanisms and structural characteristics are not yet fully understood . Besides, the OER performance depend strongly on the metal ratio such as Ni/Fe, Ni/V, Fe/V, and so on, because of the tunable morphology, electronic structure and synergistic coupling effect .…”
Section: Figurementioning
confidence: 99%
“…Recent study showed that the addition of Fe, Co or V, even in trace amount, was thought to greatly improve the OER activity of Ni-based compounds due to the enhanced conductivity and strong synergistic effect in alkaline solutions though the complete mechanisms and structural characteristics are not yet fully understood. [29][30][31][32][33] Besides, the OER performance depend strongly on the metal ratio such as Ni/Fe, Ni/V, Fe/V, and so on, because of the tunable morphology, electronic structure and synergistic coupling effect. [33,34] Recently, extensive efforts have been dedicated to the in-depth investigation of optimal metal ratios or structural phases causing higher activities.…”
mentioning
confidence: 99%